2024
DOI: 10.1680/jgein.22.00404
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a soluble subgrade on leakage through a geomembrane defect

Abstract: Leakage and erosion of a soluble subgrade overlain by a geomembrane with a 70-mm-long slit defect is examined. The subgrade (gypsum) solubility and its rate of dissolution from a solid state in contact with various solutions are investigated. In the absence of flow, the rate of dissolution is negligible. However, when there is flow there is dissolution, and if the flow is high enough, erosion. Erosion greatly increases fluid migration. The presence of an interface between the subgrade and a dissimilar material… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…Piping and internal erosion are discussed [41], as is the opening width of defective seams [42]. Finally, issues related to the subgrade imperfection on the serviceability of GMB in TSFs (i.e., tensile strain as given in [43]) and the erosion of subgrade soil containing soluble minerals like gypsum [44] are discussed. A framework diagram describing the correlation among the various research points is given in Appendix A1.…”
Section: Mechanical Properties Of Tailingsmentioning
confidence: 99%
See 1 more Smart Citation
“…Piping and internal erosion are discussed [41], as is the opening width of defective seams [42]. Finally, issues related to the subgrade imperfection on the serviceability of GMB in TSFs (i.e., tensile strain as given in [43]) and the erosion of subgrade soil containing soluble minerals like gypsum [44] are discussed. A framework diagram describing the correlation among the various research points is given in Appendix A1.…”
Section: Mechanical Properties Of Tailingsmentioning
confidence: 99%
“…Fan and Rowe (2023) [44] found that the solubility of gypsum was significant, but that the dissolution rate in contact with different solvents was extremely slow under static conditions. However, if even a small flow path existed, it was found that the rate of dissolution and erosion would increase rapidly (Figure 14).…”
Section: Soluble Subgradementioning
confidence: 99%